Chemical conversion solution, method for manufacturing electrolytic capacitor, and electrolytic capacitor
A chemical solution with phosphoric acid, phosphorous acid, and a chelating agent forms an aluminum complex to repair oxide film defects, addressing leakage current and ESR issues in electrolytic capacitors, thereby enhancing their performance.
Patent Information
- Application Number
- JP2023104488
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-26
- Publication Date
- 2025-01-15
AI Technical Summary
The manufacturing process of electrolytic capacitors results in minute defects in the oxide film, leading to increased leakage current and equivalent series resistance (ESR) due to excessive acid use, which affects the capacitor's characteristics.
A chemical solution containing phosphoric acid, phosphorous acid, hypophosphorous acid, and a chelating agent forms an aluminum complex to repair the oxide film, balancing its formation and destruction, and a conductive polymer layer is formed on a separator to improve adhesion.
The solution enhances the electrolytic capacitor's characteristics by reducing ESR and leakage current, improving the balance between repair and destruction of the oxide film, and ensuring stable conductive paths.
Smart Images

Figure 2025004655000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a chemical conversion solution, a method for manufacturing an electrolytic capacitor, and an electrolytic capacitor. [Background technology]
[0002] In a manufacturing process of an electrolytic capacitor, for example, an anode foil and a cathode foil are wound with a separator interposed therebetween. An oxide film, which is a dielectric, is formed on the surface of the wound anode foil (see, for example, Patent Documents 1 and 2). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] International Publication No. 2017 / 090241 [Patent Document 2] JP 2022-59471 A Summary of the Invention [Problem to be solved by the invention]
[0004] Since minute defects occur in the oxide film during the above-mentioned winding process, the oxide film is repaired by chemical conversion treatment. For example, in the case of solid electrolytic capacitors and hybrid capacitors, chemical conversion treatment is performed using an acidic chemical conversion solution before the conductive polymer layer is formed.
[0005] If too much acid is supplied to the surface of the anode foil at this time, the balance between repair and destruction of the oxide film may be lost, and leakage current may increase. In addition, aluminum ions eluted from the oxide film may react chemically with the acid to form poorly soluble aluminum compounds, which may block the conductive path between the oxide film and the conductive polymer layer and increase the ESR (Equivalent Series Resistance). An increase in leakage current and ESR will deteriorate the characteristics of the electrolytic capacitor.
[0006] The present invention has been made in consideration of the above problems, and an object of the present invention is to provide a chemical conversion solution that can improve the characteristics of an electrolytic capacitor, a method for manufacturing an electrolytic capacitor, and an electrolytic capacitor. [Means for solving the problem]
[0007] The chemical conversion liquid of the present invention is used to repair an aluminum oxide film formed on at least one of an anode foil and a cathode foil included in an electrolytic capacitor element, and is characterized in that it contains at least one of phosphoric acid, phosphorous acid, and hypophosphorous acid, and a chelating agent that forms an aluminum complex that bonds with the aluminum oxide film.
[0008] In the above chemical conversion solution, the electrolytic capacitor element may have a separator sandwiched between the anode foil and the cathode foil, and the aluminum complex may be bonded to a conductive polymer layer formed on the separator.
[0009] The chemical conversion solution contains at least one type of aluminum compound selected from aluminum oxide, aluminum hydroxide, aluminum carbonate, aluminum acetate, aluminum silicate, aluminum lactate, and aluminum fluoride, or aluminum, and the chelating agent may bind to the at least one type of aluminum compound or to aluminum ions ionized from the aluminum.
[0010] In the chemical conversion solution, the at least one aluminum compound or the aluminum may have a molar concentration of 0.000125 to 0.00075 mol / kg.
[0011] In the above chemical conversion solution, the electrolytic capacitor element may be impregnated with the electrolytic solution.
[0012] In the chemical conversion solution, the chelating agent may have a molar concentration of 0.0000125 to 0.000125 mol / kg.
[0013] In the chemical conversion solution, the molar concentration of at least one of the phosphoric acid, phosphorous acid, and hypophosphorous acid may be 0.0025 to 0.025 mol / kg.
[0014] In the chemical conversion solution, the chelating agent may contain at least one of nitrilotriacetic acid, ethylenediaminetetraacetic acid, glycoletherdiaminetetraacetic acid, propaminediaminetetraacetic acid, cyclohexanediaminetetraacetic acid, diethylenetriaminepentaacetic acid, and triethylenetetraminehexaacetic acid.
[0015] The method for manufacturing an electrolytic capacitor of the present invention includes the steps of forming an electrolytic capacitor element including an anode foil and a cathode foil having an aluminum oxide film formed on at least one of them, and a separator sandwiched between the anode foil and the cathode foil, and, after the step of forming the electrolytic capacitor element, repairing the aluminum oxide film using a chemical conversion solution, wherein the chemical conversion solution contains at least one of phosphoric acid, phosphorous acid, and hypophosphorous acid, and a chelating agent that forms an aluminum complex that bonds with the aluminum oxide film.
[0016] The above manufacturing method may further include a step of forming a conductive polymer layer on the separator after the step of repairing the aluminum oxide film, and the aluminum complex may be bonded to the conductive polymer layer.
[0017] The above manufacturing method may further include a step of impregnating the electrolytic capacitor element with an electrolyte solution after the step of forming the conductive polymer layer.
[0018] The electrolytic capacitor of the present invention has an electrolytic capacitor element including an anode foil and a cathode foil having an aluminum oxide film formed on at least one of them, and a separator sandwiched between the anode foil and the cathode foil, and is characterized in that at least one of phosphoric acid, phosphorous acid, and hypophosphorous acid, and an aluminum complex containing a chelating agent and aluminum hydroxide ions in a molar ratio of 1:0.1 to 1:6 are adhered to the anode foil, the cathode foil, and the separator.
[0019] In the above electrolytic capacitor, the separator may include a conductive polymer layer, and the aluminum complex may be bonded to the aluminum oxide film and the conductive polymer layer.
[0020] In the above electrolytic capacitor, the electrolytic capacitor element may be impregnated with an electrolyte solution containing the aluminum complex. Effect of the Invention
[0021] According to the present invention, the characteristics of an electrolytic capacitor can be improved. [Brief description of the drawings]
[0022] [Figure 1] FIG. 1 is a side view showing an example of an aluminum electrolytic capacitor. [Diagram 2] FIG. 2 is a perspective view showing an example of an electrolytic capacitor element. [Diagram 3] FIG. 3 is a cross-sectional view showing a part of a cross section taken along line AA in FIG. [Figure 4] FIG. 4 is a flowchart showing an example of a manufacturing process for an aluminum electrolytic capacitor. [Diagram 5] FIG. 5 is a diagram showing an example of the buffer effect against the acid in the chemical conversion solution. [Figure 6] FIG. 6 is a diagram illustrating a chemical reaction between a chelating agent, aluminum hydroxide, phosphoric acid, and water. [Figure 7] FIG. 7 is a diagram showing a schematic diagram of the bonding state between an aluminum oxide film and a conductive polymer layer. [Figure 8] FIG. 8 is a diagram showing a schematic example of the formation of an aluminum oxide film by supplying aluminum ions. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0023] [Embodiment] (Aluminum electrolytic capacitor composition) Fig. 1 is a side view showing an example of an aluminum electrolytic capacitor 1. In the right half of Fig. 1 across a center line Lc of the aluminum electrolytic capacitor 1, a cross section of the inside is shown.
[0024] The aluminum electrolytic capacitor 1 is an example of an electrolytic capacitor. In this example, a conductive polymer hybrid aluminum electrolytic capacitor (hereinafter referred to as a hybrid capacitor) is used as the aluminum electrolytic capacitor 1, but a solid electrolytic capacitor may also be used. The aluminum electrolytic capacitor 1 is mounted on an electronic circuit board and is used for, for example, coupling, decoupling, and smoothing.
[0025] The aluminum electrolytic capacitor 1 has an electrolytic capacitor element 10, a case 11, a sealing body 12, a seat plate 13, a pair of shuttlecocks 112, a pair of round bar portions 111, and a pair of lead portions 110. The shuttlecocks 112, the round bar portions 111, and the lead portions 110 are extraction electrodes of the electrolytic capacitor element 10, with the round bar portions 111 extending from the tip of the shuttlecocks 112, and the lead portions 110 extending from the tip of the round bar portions 111. Note that while only one of the shuttlecocks 112 and round bar portions 111 is shown in Fig. 1, the other shuttlecocks 112 and round bar portions 111 are provided at symmetrical positions across the center line Lc.
[0026] Case 11 is made of aluminum and has a cylindrical shape with an upper opening that is closed. Case 11 covers electrolytic capacitor element 10 and sealing body 12, and functions as an exterior of aluminum electrolytic capacitor 1. The shape of case 11 is not limited to a cylindrical shape, and may be a square tube shape.
[0027] Sealing body 12 is a generally cylindrical member made of an elastic member such as butyl rubber. Sealing body 12 is adjacent to electrolytic capacitor element 10 and seals the opening at the bottom of case 11.
[0028] As described below, the electrolytic capacitor element 10 has a configuration in which an anode foil, a cathode foil, and a separator (electrolytic paper) are overlapped and wound. A pair of shuttlecock parts 112 are disposed inside the electrolytic capacitor element 10, and a pair of round bar parts 111 extend from the bottom of the electrolytic capacitor element 10.
[0029] The shuttlecock portion 112, the round bar portion 111, and the lead portion 110 are formed from aluminum or the like. The pair of shuttlecock portions 112 are crimped to the anode foil and the cathode foil, respectively, and function as the anode terminal and the cathode terminal of the aluminum electrolytic capacitor 1. Each of the round bar portions 111 is inserted into a pair of through holes 120 formed in the sealing body 12. Although only one of the through holes 120 is shown in FIG. 1, the other through hole 120 is provided at a symmetrical position across the center line L.
[0030] The lead portion 110 has a flat plate shape and is bent into an L shape, with its tip portion extending along the plate surface of the base plate 13. The portion of the lead portion 110 on the round bar portion 111 side is inserted into a through hole 130 of the base plate 13. The lead portion 110 is soldered to a pad on the electronic circuit board in the reflow process of the electronic circuit board.
[0031] The seat plate 13 is a plate-like member made of resin or the like, and is provided under the case 11 and the sealing body 12. The seat plate 13 supports the case 11 and the sealing body 12 with respect to the electronic circuit board to which the capacitor is to be mounted. The seat plate 13 is provided with a through hole 130 for the lead portion 110 and a groove portion 131 for accommodating the bent tip portion of the lead portion 110. The groove portion 131 extends from near the center to the outside along the bottom surface of the seat plate 13. The bottom surface of the seat plate 13 is the mounting surface of the aluminum electrolytic capacitor 1 with respect to the electronic circuit board, so that the plate-like lead portion 110 can be soldered to a pad on the electronic circuit board. Note that, although the present embodiment describes a surface-mount type aluminum electrolytic capacitor 1, the examples described below can also be applied to a lead type without the seat plate 13.
[0032] (Structure of electrolytic capacitor element) Fig. 2 is a perspective view showing an example of an electrolytic capacitor element 10. In Fig. 2, components common to Fig. 1 are given the same reference numerals, and their description will be omitted. Fig. 2 shows a state before the lead portion 110 is bent. The electrolytic capacitor element 10 has a wound body 100 in which an anode foil 101, a cathode foil 102, and separators 103 and 104 are wound, and a pair of extraction electrodes 19a and 19b connected to the anode foil 101 and the cathode foil 102. The extraction electrode 19a is an anode side terminal, and the extraction electrode 19b is a cathode side terminal.
[0033] The anode foil 101 and the cathode foil 102 are formed of, for example, aluminum and its alloy foil, evaporated foil, or the like. The surface of the anode foil 101 is etched to increase the electrode area. This ensures that the electrolytic capacitor element 10 has a predetermined capacitance. Furthermore, an extremely thin aluminum oxide film is formed on the surface of the anode foil 101 as an oxide film. This insulates the anode foil 101 from other members. The aluminum oxide film functions as a dielectric, allowing the electrolytic capacitor element 10 to function as a capacitor. The thickness of the anode foil 101 is, for example, 5 to 200 (μm). This thickness range is preferable because it allows an appropriate balance to be achieved between the strength of the anode foil 101 and the amount of capacitance developed.
[0034] The surface of the cathode foil 102 may also be etched. An oxide film, an inorganic layer, or a carbon layer may be formed on the surface of the cathode foil 102.
[0035] The separators 103 and 104 are wound in a state sandwiched between the anode foil 101 and the cathode foil 102. The wound body 100 is an example of a layered structure of the separators 103 and 104, the anode foil 101, and the cathode foil 102. The separators 103 and 104 are made of at least one material selected from cellulose, rayon, glass fiber, and the like. The wound body 100 is a substantially cylindrical element formed by winding the anode foil 101, the cathode foil 102, and the separators 103 and 104. In this embodiment, the height direction of the electrolytic capacitor element 10 is defined along the height of this substantially cylindrical shape. The pair of extraction electrodes 19a and 19b extend downward of the wound body 100 in the height direction. The height direction substantially coincides with the direction in which the round bar portions 111 of the extraction electrodes 19a and 19b extend.
[0036] The wound body 100 is immersed in a dispersion or solution of an electrolytic solution and a conductive polymer in the manufacturing process of the aluminum electrolytic capacitor 1. This causes the separators 103, 104 to hold the electrolytic solution and the conductive polymer layer. In the case of a solid electrolytic capacitor, the electrolytic solution is not held. The thickness of the separators 103, 104 is, for example, 1 to 100 (μm). This thickness range is preferable because it maintains a good balance between the strength, insulation, porosity, and conductive material of the separators 103, 104.
[0037] The electrolyte may contain polyhydric alcohols, sulfone compounds, lactone compounds, carbonate compounds, diether compounds of polyhydric alcohols, monohydric alcohols, etc. These may be used alone or in combination.
[0038] The polyhydric alcohol preferably contains at least one of ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, butanediol, polyalkylene glycol, and glycerin. As the polyalkylene glycol, it is preferable to use polyethylene glycol having an average molecular weight of 200 to 1000 or polypropylene glycol having an average molecular weight of 200 to 5000.
[0039] Examples of the lactone compound include γ-butyrolactone and γ-valerolactone. Examples of the carbonate compound include dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, ethylene carbonate, propylene carbonate, and fluoroethylene carbonate as a solvent. In particular, it is preferable to use ethylene glycol, polyalkylene glycol, γ-butyrolactone, and sulfolane.
[0040] The electrolyte may contain a solute, such as an acid component, a base component, a salt of an acid component and a base component, a nitro compound, or a phenol compound.
[0041] The acid component may be an organic acid, an inorganic acid, or a composite compound of an organic acid and an inorganic acid. The organic acid may be a carboxylic acid such as phthalic acid, isophthalic acid, terephthalic acid, maleic acid, succinic acid, glutaric acid, adipic acid, benzoic acid, 4-hydroxybenzoic acid, 1,6-decanedicarboxylic acid, 1,7-octanedicarboxylic acid, or azelaic acid. The inorganic acid may be boric acid, phosphoric acid, phosphorous acid, hypophosphorous acid, phosphoric acid ester, or phosphoric acid diester.
[0042] Examples of the composite compound of an organic acid and an inorganic acid that can be used include borodisalicylic acid, borodisalic acid, and borodiglycolic acid.
[0043] The base component may be a primary to tertiary amine, a quaternary ammonium, a quaternary amidinium, etc. The primary to tertiary amine may be, for example, methylamine, dimethylamine, trimethylamine, ethylamine, diethylamine, triethylamine, ethylenediamine, N,N-diisopropylethylamine, tetramethylethylenediamine, hexamethylenediamine, aniline, etc. The quaternary ammonium may be, for example, tetramethylammonium, triethylmethylammonium, tetraethylammonium, etc. The quaternary amidinium may be, for example, ethyldimethylimidazolinium, tetramethylimidazolinium, etc.
[0044] Fig. 3 is a cross-sectional view showing a portion of a cross section taken along line AA in Fig. 2. Separator 103 is sandwiched between anode foil 101 and cathode foil 102. Anode foil 101 has aluminum oxide films 31 adjacent to separators 103 on both sides, and aluminum layers 30 between each aluminum oxide film 31.
[0045] Aluminum oxide film 31 functions as a dielectric and is formed on the etched surface of anode foil 101. A large number of small holes, called pits, are formed in aluminum oxide film 31 by etching. When electrolytic capacitor element 10 is immersed in an electrolyte in the manufacturing process of aluminum electrolytic capacitor 1, the electrolyte fills not only separator 103 but also the pits.
[0046] Prior to the immersion in the electrolyte, a conductive polymer immersion process is performed. By immersing the electrolytic capacitor element 10 in the conductive polymer dispersion, a conductive polymer layer 40 is formed on the separator 103. Note that, although an example in which the aluminum oxide film 31 is formed on the anode foil 101 is given in this embodiment, an aluminum oxide film may be formed on the cathode foil 102 instead of the anode foil 101 or together with the anode foil 101.
[0047] (Aluminum electrolytic capacitor manufacturing process) 4 is a flowchart showing an example of a manufacturing process for aluminum electrolytic capacitor 1. In manufacturing aluminum electrolytic capacitor 1, anode foil 101, cathode foil 102, separator 103, and the like are prepared (step St1). For example, anode foil 101 has a thickness of 5 to 200 (μm), and separator has a thickness of 1 to 100 (μm). Pits are formed on the surfaces of anode foil 101 and cathode foil 102 by etching.
[0048] A chemical conversion treatment is applied to the anode foil 101, and an aluminum oxide film 31 is formed on the etched surface. A pair of lead electrodes 19a, 19b are connected to the anode foil 101 and the cathode foil 102, respectively. Means for connecting the lead electrodes 19a, 19b include, but are not limited to, crimping.
[0049] Next, the anode foil 101, the separator 103, the cathode foil 102, and the separator 103 are laminated in this order and wound, and the outer surface is fixed with a winding stop tape to generate the wound body 100 (step St2). In this way, the electrolytic capacitor element 10 is generated in a stage prior to immersion in the conductive polymer solution and the electrolyte solution. At this time, minute defects are generated in the aluminum oxide film 31 due to the attachment of the lead electrodes 19a, 19b to the anode foil 101 and the above-mentioned winding. Note that this step is an example of a step of forming the electrolytic capacitor element 10 including the anode foil 101 and the cathode foil 102 having the aluminum oxide film 31 formed on at least one side thereof, and the separator 103 sandwiched between the anode foil 101 and the cathode foil 102.
[0050] Next, the wound body 100 is immersed in a chemical conversion solution, and a chemical re-conversion process is performed while applying a predetermined voltage to the anode foil 101 (step St3). This repairs minute defects in the aluminum oxide film 31. Also, an aluminum oxide film is formed on the surfaces of the cut edges (ends) of the anode foil 101 in the vertical direction. The chemical re-conversion process is an example of a process for repairing the aluminum oxide film 31.
[0051] The chemical conversion solution contains water as a solvent and at least the following components: The effects of the chemical conversion solution will be described in detail later. At least one of phosphoric acid, phosphorous acid, and hypophosphorous acid (hereinafter referred to as acid) Chelating agent that forms an aluminum complex that binds to the aluminum oxide film 31 At least one aluminum compound selected from the group consisting of aluminum oxide, aluminum hydroxide, aluminum carbonate, aluminum acetate, aluminum silicate, aluminum lactate, and aluminum fluoride, or aluminum
[0052] Next, in a reduced pressure atmosphere, the wound body 100 is immersed in a dispersion liquid of a conductive polymer to impregnate the wound body 100 with the dispersion liquid (step St4). Note that the wound body 100 may be immersed in a solution containing a conductive polymer instead of the dispersion liquid of the conductive polymer.
[0053] Next, the wound body 100 is dried (step St5). At this time, the water, which is the solvent of the conductive polymer liquid impregnated in the separator 103 in the wound body 100, evaporates, and the nanoparticles form the conductive polymer layer 40. The processes of steps St4 and St5 are an example of a process of forming the conductive polymer layer 40 on the separators 103 and 104.
[0054] Next, electrolytic capacitor element 10 is impregnated with the electrolyte in a reduced pressure atmosphere (step St6). Next, electrolytic capacitor element 10 is housed in case 11 and sealed with sealing body 12 (step St7). At this time, extraction electrodes 19a, 19b extending from electrolytic capacitor element 10 are inserted into through holes 120 of sealing body 12. Thereafter, aging treatment may be performed while applying a rated voltage to aluminum electrolytic capacitor 1. In this manner, the manufacturing process for aluminum electrolytic capacitor 1 is performed. Note that the manufacturing process for aluminum electrolytic capacitor 1 is one example of a manufacturing method for aluminum electrolytic capacitor 1.
[0055] (Effect of chemical conversion solution) Fig. 5 is a diagram showing an example of the buffering effect against an acid in a chemical conversion solution. Fig. 5 is a schematic diagram showing a state of a chemical reaction in the vicinity of the surface of an anode foil 101 without an aluminum oxide film 31. Note that, in this embodiment, an example is given in which an aluminum oxide film 31 formed on an anode foil 101 is repaired, but the following effects can also be obtained in the case of repairing an aluminum oxide film formed on a cathode foil 102 instead of or together with the anode foil 101.
[0056] As shown by symbol G1a, hydronium ions (HO + ) occurs, and when a voltage is applied in the re-chemical conversion treatment, the aluminum (element) of the anode foil 101 is positively charged. Therefore, the unshared electron pair of the hydronium ion is attracted to the aluminum.
[0057] Next, as shown by the symbol G1b, aluminum bonds with hydronium ions, and aluminum hydroxide (Al(OH)3) is generated as H2 moves to the cathode foil 102 side. As a result, the outermost layer of the anode foil 101 is covered with OH groups.
[0058] Next, as shown by the symbol G1c, aluminum ions (Al + ) bonds with the OH groups on the outermost layer of the anode foil 101. This forms an aluminum oxide (Al2O3) film 31. Hydrogen is generated by the bonding of aluminum ions.
[0059] Next, as shown by the reference symbol G1d, the hydronium ions act on the aluminum oxide film 31, destroying the aluminum oxide film 31. As a result, the aluminum oxide film 31 returns to aluminum hydroxide.
[0060] In this way, the formation (i.e., repair) and destruction of the aluminum oxide film 31 are repeated due to the action of the acid. At this time, if an excessive amount of acid is supplied to the surface of the anode foil 101, the balance between the repair and destruction of the aluminum oxide film 31 is lost, and there is a risk of an increase in leakage current.
[0061] However, the chelating agent in the chemical conversion solution acts as a buffer against the acid because it forms an aluminum complex that bonds with the aluminum oxide film 31. In this embodiment, the chelating agent is, but is not limited to, triethylenetetraminehexaacetic acid (TTHA).
[0062] As indicated by the symbol G1e, an aluminum complex of TTHA binds to the aluminum oxide film 31. As a result, the surface of the aluminum oxide film 31 is covered with a coating 32 of the aluminum complex, suppressing destruction of the aluminum oxide film 31 by hydronium ions. In addition, since TTHA absorbs and releases acid, it is possible to adjust the amount of acid on the surface of the anode foil 101 to an appropriate level. Therefore, it is possible to maintain a balance between repair and destruction of the aluminum oxide film 31 by the chelating agent, thereby reducing leakage current.
[0063] 6 is a diagram showing a schematic diagram of a chemical reaction between a chelating agent, aluminum hydroxide, phosphoric acid, and water. For example, when phosphoric acid (H3PO4) is contained as an acid in the chemical conversion solution, the aluminum hydroxide on the surface of the anode foil 101 dissolves, generating poorly soluble aluminum phosphate (Al3PO4), which inhibits the ionization of aluminum. Furthermore, the aluminum phosphate crystallizes and prevents the conductive polymer layer 40 from adhering to the aluminum oxide film 31, suppressing the formation of a conductive path and increasing the ESR. This is also true when the chemical conversion solution contains phosphorous acid and hypophosphorous acid instead of or together with phosphoric acid.
[0064] However, TTHA chemically reacts with aluminum hydroxide, phosphoric acid, and water to form an aluminum complex, thereby generating aluminum ions. This improves the reactivity of the chemical conversion solution, accelerating the formation and repair of the aluminum oxide film 31. In addition, the formation of aluminum phosphate is suppressed, improving the adhesion of the conductive polymer layer 40 and reducing the ESR of the aluminum electrolytic capacitor 1.
[0065] 7 is a diagram showing a schematic diagram of the bonding state between the aluminum oxide film 31 and the conductive polymer layer 40. The conductive polymer layer 40 of this embodiment contains polyethylene sulfonic acid.
[0066] As shown by the reference symbol G2a, the OH groups of the aluminum oxide film 31 on the surface of the anode foil 101 are separated and bonded with the sulfonate ions of the polyethylene sulfonic acid to form a conductive path. However, since the surface of the anode foil 101 has a complex uneven shape due to the etching process, the conductive path is not necessarily stable. In addition, in the case of a hybrid capacitor, there is a risk that the aluminum oxide film 31 and the conductive polymer layer 40 will be separated by the electrolyte impregnated in the separators 103 and 104.
[0067] TTHA forms an aluminum complex, and as shown by the symbol G2b, the COO group of the aluminum complex is strongly bonded to the aluminum oxide film 31. As a result, the aluminum complex adheres to the surface of the anode foil 101. Meanwhile, the aluminum complex is bonded to the sulfonate ion via the aluminum ion. As a result, the aluminum oxide film 31 and the conductive polymer layer 40 are strongly bonded to each other via the aluminum complex. This improves the adhesion of the conductive polymer layer 40 and enhances the formation of a conductive path, thereby reducing the ESR of the aluminum electrolytic capacitor 1.
[0068] 8 is a diagram showing a schematic example of the formation of an aluminum oxide film 31 by supplying aluminum ions. Since the chemical conversion solution contains one type of aluminum compound or aluminum, as shown by symbol G3a, TTHA bonds with the aluminum compound or the aluminum ions ionized from aluminum to form an aluminum complex even in the absence of aluminum ions eluted from the anode foil 101 by phosphoric acid.
[0069] Next, as shown by reference symbol G3b, aluminum ions are supplied to the OH groups of the aluminum hydroxide of the anode foil 101. This forms an aluminum oxide film 31 on the surface of the anode foil 101. Thereafter, as shown by reference symbol G3c, the aluminum complex returns to TTHA, leaving Al-OH on the surface of the anode foil 101, but it combines with the aluminum ions again to repeat the above reaction. Therefore, TTHA functions as a catalyst to form the aluminum oxide film 31.
[0070] In this way, the chemical reaction actively proceeds due to the aluminum ions in the chemical conversion solution. Therefore, compared to a case where there are no aluminum ions in the chemical conversion solution, the aluminum oxide film 31 is formed more densely. This prevents the aluminum oxide film 31 and the conductive polymer layer 40 from peeling off together, making it possible to extend the life of the aluminum electrolytic capacitor 1. In this way, the chemical conversion solution of this embodiment improves the characteristics of the aluminum electrolytic capacitor 1.
[0071] In this embodiment, TTHA is used as the chelating agent, but is not limited thereto. The chelating agent may contain at least one of nitrilotriacetic acid, ethylenediaminetetraacetic acid, glycoletherdiaminetetraacetic acid, propaminediaminetetraacetic acid, cyclohexanediaminetetraacetic acid, diethylenetriaminepentaacetic acid, and triethylenetetraminehexaacetic acid. This allows the aluminum complex to be formed more stably than a monodentate complex.
[0072] Furthermore, it is preferable that the molar concentration of the chelating agent in the chemical conversion solution is 0.00001 to 0.000125 mol / kg, as this favorably improves the characteristics of the aluminum electrolytic capacitor 1. It is also preferable that the molar concentration of the aluminum compound or aluminum in the chemical conversion solution is 0.0000125 to 0.00075 mol / kg, as this favorably improves the characteristics of the aluminum electrolytic capacitor 1. It is also preferable that the molar concentration of at least one of phosphoric acid, phosphorous acid, and hypophosphorous acid in the chemical conversion solution is 0.0025 to 0.025 mol / kg, as this favorably improves the characteristics of the aluminum electrolytic capacitor 1.
[0073] The electrolytic capacitor element 10 of the aluminum electrolytic capacitor 1 contains residues of the above-mentioned chemical conversion solution. At least one of phosphoric acid, phosphorous acid, and hypophosphorous acid, and an aluminum complex containing a chelating agent and aluminum hydroxide ions in a molar ratio of 1:0.1 to 1:6 are attached to the anode foil 101, the cathode foil 102, and the separator 103. This molar ratio allows the balance between repair and destruction of the aluminum oxide film 31 to be in a metastable state, thereby reducing the ESR and leakage current of the aluminum electrolytic capacitor 1.
[0074] Separators 103, 104 contain an aluminum complex bonded to aluminum oxide film 31. The aluminum complex is bonded to aluminum oxide film 31 and conductive polymer layer 40. As a result, aluminum oxide film 31 and conductive polymer layer 40 are firmly bonded together, as described above, and peeling due to the electrolytic solution is suppressed. In the case of a hybrid capacitor, the electrolytic solution impregnated in electrolytic capacitor element 10 contains an aluminum complex, so that the aluminum complex can be suitably distributed throughout electrolytic capacitor element 10, and the characteristics of aluminum electrolytic capacitor 1 can be improved by the above-mentioned action and effect. EXAMPLES
[0075] Samples No. 1 to 16 of the aluminum electrolytic capacitor 1 were produced. Samples No. 1 to 8 were solid electrolytic capacitors, and Samples No. 9 to 16 were hybrid capacitors. Samples No. 9 to 16 were produced according to the above manufacturing process, and Samples No. 1 to 8 were produced according to the above manufacturing process except for step St6. The diameter of the case 11 of Samples No. 1 to 16 was 10 (mm), and the size in the height direction of Samples No. 1 to 16 was 10 (mm). The rated voltage and capacitance (nominal value) of Samples No. 1 to 16 were 80 (V) and 47 (μF), respectively.
[0076] An aqueous dispersion of a composite product (PEDOT:PSS) made of poly(3,4-ethylenedioxythiophene) and polystyrenesulfonic acid was used as the polymer dispersion liquid for forming the conductive polymer layer 40. An ethylene glycol-based electrolyte was used.
[0077] [Table 1]
[0078] Table 1 shows the molar mass concentration (mol / kg), conductivity (μS / cm), and hydrogen ion exponent (pH) of each component of Sample No. 1 to 16. For the re-chemical conversion treatment of Sample No. 2, 4 to 8, 10, and 12 to 16, a chemical conversion solution in which phosphoric acid, TTHA, aluminum hydroxide, and ammonia were mixed with water as a solvent was used. For the re-chemical conversion treatment of Sample No. 1 and 9, a chemical conversion solution in which phosphoric acid and ammonia were mixed with water as a solvent and did not contain TTHA or aluminum hydroxide was used as a comparative example. For the re-chemical conversion treatment of Sample No. 3 and 11, a chemical conversion solution in which TTHA, phosphoric acid, and ammonia were mixed with water as a solvent and did not contain aluminum hydroxide was used. In the chemical conversion treatment, electrolytic capacitor element 10 in which anode foil 101 and cathode foil 102 were wound with separators 103 and 104 interposed therebetween was immersed in the chemical conversion solution.
[0079] The TTHA molar concentration of samples Nos. 2 and 10 was 0.00001 mol / kg, and the TTHA molar concentration of samples Nos. 3, 4, 11, and 12 was 0.0000125 mol / kg. The TTHA molar concentration of samples Nos. 5, 6, 13, and 14 was 0.000125 mol / kg, and the TTHA molar concentration of samples Nos. 7, 8, 15, and 16 was 0.00015 mol / kg.
[0080] The mass molar concentrations of phosphoric acid in Samples Nos. 1, 3, 4, 9, 11, and 12 were 0.0025 mol / kg, and the mass molar concentrations of phosphoric acid in Samples Nos. 2 and 10 were 0.002 mol / kg. The mass molar concentrations of phosphoric acid in Samples Nos. 5 to 7 and 13 to 15 were 0.025 mol / kg, and the mass molar concentrations of phosphoric acid in Samples Nos. 8 and 16 were 0.03 mol / kg.
[0081] The molar mass concentration of aluminum hydroxide in samples Nos. 2 and 10 was 0.00001 mol / kg, and the molar mass concentration of aluminum hydroxide in samples Nos. 4, 5, 12, and 13 was 0.0000125 mol / kg. The molar mass concentration of aluminum hydroxide in samples Nos. 6 and 14 was 0.00075 mol / kg, and the molar mass concentration of aluminum hydroxide in samples Nos. 7, 8, 15, and 16 was 0.0009 mol / kg.
[0082] The mass molar concentration of ammonia in Samples Nos. 1, 3, 4, 9, 11, and 12 was 0.005 mol / kg, and the mass molar concentration of ammonia in Samples Nos. 2 and 10 was 0.004 mol / kg. The mass molar concentration of ammonia in Samples Nos. 5 to 7 and 13 to 15 was 0.05 mol / kg, and the mass molar concentration of ammonia in Samples Nos. 8 and 16 was 0.06 mol / kg. In this way, the hydrogen ion exponent of each chemical conversion solution was adjusted to less than pH 7.
[0083] Regarding the electrical conductivity of the chemical conversion solution for the solid electrolytic capacitors, sample No. 3 had the smallest, and sample No. 1 had the second smallest. Sample No. 8 also had the largest electrical conductivity. Meanwhile, regarding the electrical conductivity of the chemical conversion solution for the hybrid capacitors, sample No. 11 had the smallest, and sample No. 9 had the second smallest. Sample No. 16 also had the largest electrical conductivity.
[0084] [Table 2]
[0085] [Table 3]
[0086] Table 2 shows the evaluation results of samples No. 1 to 8 of the solid electrolytic capacitor, and Table 3 shows the evaluation results of samples No. 9 to 16 of the hybrid capacitor. In the evaluation, a load test was performed at 150°C and an applied voltage of 80 (V), and the capacitance (μF), loss angle (tan δ), ESR (Ω), and leakage current (μA) were measured in an initial state of aluminum electrolytic capacitor 1 in an environment of 20°C and after 1000 hours from the start of voltage application. The capacitance, loss angle, and ESR were measured with an LCR meter, and the leakage current was measured by connecting a resistor between the positive side of a DC power supply and the anode terminal of samples No. 1 to 16, measuring the voltage at both ends with a data logger for 1 minute and converting it into an average current value. In addition, the capacitance ratio ΔC / Co (%) was calculated from the capacitance reduction ΔC (<0) after 1000 hours relative to the capacitance Co in the initial state.
[0087] Samples No. 1 and No. 9 were compared with other samples No. 2 to 8, 10 to 16 as comparative examples not containing TTHA. In Table 1, if the ESR and leakage current were lower than that of sample No. 1, it was judged as "OK", and if they were equal to or higher than sample No. 1, it was judged as "NG". Similarly, in Table 2, if the ESR and leakage current were lower than that of sample No. 9, it was judged as "OK", and if they were equal to or higher than sample No. 9, it was judged as "NG".
[0088] As for the solid electrolytic capacitor, in sample No. 1, a sufficient conductive path was not formed compared to other samples No. 2 to 8 containing TTHA, and the aluminum oxide film 31 was not sufficiently repaired. On the other hand, in samples No. 2 to 8, a sufficient conductive path was formed by the action of TTHA, and the aluminum oxide film 31 was sufficiently repaired. Therefore, the ESR and leakage current of samples No. 2 to 8 after 1000 hours were lower than that of sample No. 1. Therefore, the judgment of samples No. 2 to 8 was "OK". In addition, the loss angle of samples No. 2 to 8 was also lower than that of sample No. 1. In addition, the capacitance ratio (absolute value) of sample No. 1 was smaller than that of samples No. 2 to 8 because a sufficient dielectric constant was not obtained due to the lack of TTHA.
[0089] As for the hybrid capacitor, the ESR and leakage current of Samples No. 10 to 16 after 1000 hours were lower than that of Sample No. 9 for the same reasons as above. Therefore, Samples No. 10 to 16 were judged as "OK". The loss angles of Samples No. 10 to 16 were also lower than that of Sample No. 9. The capacitance ratio (absolute value) of Sample No. 9 was smaller than that of Samples No. 10 to 16 because a sufficient dielectric constant could not be obtained due to the absence of TTHA.
[0090] After 1000 hours, the ESR, leakage current, and loss angle of Sample Nos. 7 and 8 were larger than those of Sample Nos. 4 to 6, and the ESR, leakage current, and loss angle of Sample Nos. 15 and 16 were larger than those of Sample Nos. 12 to 14. This is thought to be because the molar concentration of TTHA in Sample Nos. 7, 8, 15, and 16 was larger than those in Sample Nos. 4 to 6 and 12 to 14, and the large amount of TTHA inhibited the formation of a conductive path.
[0091] Moreover, the ESR, leakage current, and loss angle of sample No. 2 after 1000 hours are larger than those of samples No. 4 to 6, and the ESR, leakage current, and loss angle of sample No. 10 after 1000 hours are larger than those of samples No. 12 to 14. This is considered to be because the molar concentration of TTHA in samples No. 2 and 10 is smaller than those of samples No. 4 to 6 and 12 to 14, and there are fewer conductive paths, and the conductive paths are cut off as the destruction of the aluminum oxide film 31 progresses. Therefore, the molar concentration of TTHA is preferably 0.0000125 to 0.000125 mol / kg.
[0092] Moreover, the ESR, leakage current, and loss angle of sample No. 4 after 1000 hours are smaller than those of sample No. 3, and the ESR, leakage current, and loss angle of sample No. 12 after 1000 hours are smaller than those of sample No. 11. Since the chemical conversion solution used for samples Nos. 4 and 12 contains aluminum hydroxide, as described above, aluminum ions ionized from the aluminum hydroxide form aluminum oxide film 31 more densely than those of samples Nos. 3 and 11, and the ESR and loss angle are reduced.
[0093] The ESR of samples Nos. 7 and 8 is greater than that of samples Nos. 4 to 6, and the ESR of samples Nos. 15 and 16 is greater than that of samples Nos. 12 to 14. This is because if there is too much aluminum hydroxide, the TTHA layer formed on the surface of aluminum oxide film 31 becomes thicker, cutting off the conductive path.
[0094] Moreover, the ESR of sample No. 2 is greater than that of samples No. 4 to 6, and the ESR of sample No. 10 is greater than that of samples No. 12 to 14. This is because if the amount of aluminum hydroxide is too small, the amount of conductive polymer attached to the aluminum complex becomes insufficient.
[0095] Therefore, the molar concentration of aluminum hydroxide is preferably 0.000125 to 0.00075 mol / kg. The molar ratio of soluble TTHA to aluminum hydroxide is 1:0.1 to 1:6, and this ratio makes it possible to keep the balance between destruction and repair of the aluminum oxide film 31 in a quasi-stable state.
[0096] Furthermore, it is preferable that the molar concentration of at least one of the phosphoric acids is 0.0025 to 0.025 mol / kg, since this reduces the ESR, leakage current, and loss angle as in Samples Nos. 4 to 6 and 12 to 14. If the molar concentration of the phosphoric acid is less than 0.0025 mol / kg, OH groups are less likely to be generated on the surface of the anode foil 101, whereas if the molar concentration of the phosphoric acid is more than 0.025 mol / kg, the attack of the phosphoric acid on the aluminum oxide film 31 becomes too strong, reducing the withstand pressure of the chemical conversion solution.
[0097] Although the embodiments of the present invention have been described in detail above, the present invention is not limited to such specific embodiments, and various modifications and variations are possible within the scope of the gist of the present invention described in the claims. [Explanation of symbols]
[0098] 1. Aluminum electrolytic capacitor 10 Electrolytic capacitor element 31 Aluminum oxide film 40 Conductive polymer layer 100 rolls 101 Anode foil 102 Cathode foil 103,104 Separator
Claims
1. A chemical conversion solution used for repairing an aluminum oxide film formed on at least one of an anode foil and a cathode foil included in an electrolytic capacitor element, At least one of phosphoric acid, phosphorous acid, and hypophosphorous acid; a chelating agent that forms an aluminum complex that bonds with the aluminum oxide film.
2. the electrolytic capacitor element includes a separator sandwiched between the anode foil and the cathode foil, The chemical conversion solution according to claim 1 , wherein the aluminum complex is bonded to a conductive polymer layer formed on the separator.
3. Contains at least one aluminum compound selected from aluminum oxide, aluminum hydroxide, aluminum carbonate, aluminum acetate, aluminum silicate, aluminum lactate, and aluminum fluoride, or aluminum; 3. The chemical conversion solution according to claim 1, wherein the chelating agent is bonded to the at least one aluminum compound or to aluminum ions ionized from the aluminum.
4. 4. The chemical conversion solution according to claim 3, wherein the at least one aluminum compound or the aluminum has a molar mass concentration of 0.000125 to 0.00075 mol / kg.
5. 3. The chemical conversion solution according to claim 1, wherein the electrolytic capacitor element is impregnated with an electrolyte.
6. 5. The chemical conversion solution according to claim 4, wherein the chelating agent has a molar concentration of 0.0000125 to 0.000125 mol / kg.
7. 5. The chemical conversion solution according to claim 4, wherein the molar mass concentration of at least one of the phosphoric acid, the phosphorous acid, and the hypophosphorous acid is 0.0025 to 0.025 mol / kg.
8. 3. The chemical conversion solution according to claim 1, wherein the chelating agent contains at least one of nitrilotriacetic acid, ethylenediaminetetraacetic acid, glycoletherdiaminetetraacetic acid, propaminediaminetetraacetic acid, cyclohexanediaminetetraacetic acid, diethylenetriaminepentaacetic acid, and triethylenetetraminehexaacetic acid.
9. forming an electrolytic capacitor element including an anode foil and a cathode foil, at least one of which has an aluminum oxide film formed thereon, and a separator sandwiched between the anode foil and the cathode foil; and after the step of forming the electrolytic capacitor element, a step of repairing the aluminum oxide film by using a chemical conversion solution, The chemical conversion solution is At least one of phosphoric acid, phosphorous acid, and hypophosphorous acid; and a chelating agent that forms an aluminum complex that bonds with the aluminum oxide film.
10. and forming a conductive polymer layer on the separator after the step of repairing the aluminum oxide film. The method for producing an electrolytic capacitor according to claim 9 , wherein the aluminum complex is bonded to the conductive polymer layer.
11. 10. The method for producing an electrolytic capacitor according to claim 9, further comprising the step of impregnating the electrolytic capacitor element with an electrolytic solution after the step of forming the conductive polymer layer.
12. an electrolytic capacitor element including an anode foil and a cathode foil, at least one of which has an aluminum oxide film formed thereon, and a separator sandwiched between the anode foil and the cathode foil; The anode foil, the cathode foil, and the separator include At least one of phosphoric acid, phosphorous acid, and hypophosphorous acid; An electrolytic capacitor comprising an aluminum complex having a chelating agent and aluminum hydroxide ions in a molar ratio of 1:0.1 to 1:6 attached thereto.
13. The separator includes a conductive polymer layer, 13. The electrolytic capacitor according to claim 12, wherein the aluminum complex is bonded to the aluminum oxide film and the conductive polymer layer.
14. 14. The electrolytic capacitor according to claim 12, wherein the electrolytic capacitor element is impregnated with an electrolyte solution containing the aluminum complex.
Citation Information
Patent Citations
Solid electrolytic capacitor and manufacturing method thereof
JP2022059471A
Electrolytic capacitor and method for manufacturing same
WO2017090241A1
Cited By
Compositions and methods for application over skin
US12419906B2